2018
DOI: 10.1016/j.biortech.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulphur on the performance of an anaerobic membrane bioreactor: Biological stability, trace organic contaminant removal, and membrane fouling

Abstract: This study investigated the impact of sulphur content on the performance of an anaerobic membrane bioreactor (AnMBR) with an emphasis on the biological stability, contaminant removal, and membrane fouling. Removal of 38 trace organic contaminants (TrOCs) that are ubiquitously present in municipal wastewater by AnMBR was evaluated. Results show that basic biological performance of AnMBR regarding biomass growth and the removal of chemical oxygen demand (COD) was not affected by sulphur addition when the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Song et al, [86] examined the effect of sulphate concentration on the performance of AnMBR and reported that basic biological performance of AnMBR was not impacted by the increasing sulphate concentration when the influent COD/SO4 2ratio was maintained at higher than 10.…”
Section: Inhibitory Substancesmentioning
confidence: 99%
“…Song et al, [86] examined the effect of sulphate concentration on the performance of AnMBR and reported that basic biological performance of AnMBR was not impacted by the increasing sulphate concentration when the influent COD/SO4 2ratio was maintained at higher than 10.…”
Section: Inhibitory Substancesmentioning
confidence: 99%
“…Flux decay ranged from 52% to 72%, and the ultrafiltration was found to not have any measurable effect. Song et al (2018) reported that AnMBR performance with respect to biomass growth and COD removal remained unaffected by sulfur addition as long as the COD:Sulfate ratio was higher than 10:1.…”
Section: Membrane Treatment Technologiesmentioning
confidence: 99%
“…Song vd. [19], yüksek sülfat konsantrasyonunun (> 200 mg/L), yukarı akışlı anaerobik çamur yataklı reaktörün işletimi sırasında, anaerobik çürütücülerden SMP ve EPS'nin ana bileşenleri olan karbonhidrat ve proteinin salınımını önemli ölçüde arttırabildiğini bildirmiştir. Hem SMP hem de EPS, aerobik veya anaerobik MBR sistemlerinde gözenek tıkanıklığında ve membran yüzeyinde kek tabakasının oluşumunda önemli bir rol oynar.…”
Section: Akı Tmp Membran Direnci Değişimleri Ve Kirlenme Oranlarıunclassified